Perlindungan Hukum Terhadap Pemegang Hak Cipta Terkait Kegiatan Streaming Dan Download Film Bajakan Melalui Website Ilegal - Anak Agung Gde Chandra Wiratama; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Warmadewa Press, 2022)
Currently, there are many pirated films that are circulated in Indonesia, which use the internet to provide illegal websites that can be freely accessed by the public, regardless of the rights of the creator of the film being harmed. Unscrupulous website makers/providers of pirated films sometimes cheat by changing their names or website domains to deceive those who enforce the law in implementing their duties. The purpose of this research is to find out the consequences of the laws that arise for streaming and downloading pirated films through illegal websites. This research is a normative legal research using a statute approach and a case approach. Sources of data used in the form of primary data and secondary data. Data were analyzed using qualitative methods. Based on the data that has been analyzed, it shows that the form of legal protection for moral rights and economic rights of those who hold film copyrights for illegal downloading and broadcasting activities by other parties seen from the form of preventive protection with the 2014 UUHC made by the government can be interpreted as a form of protection. preventive measures to prevent violations of the rights of film creators and forms of repressive legal protection such as firm actions in the form of closing/blocking illegal websites and civil lawsuits by way of compensation, it can also be criminal prosecution depending on the active role of the creator or copyright holder of the film work.